Pola Komunikasi Melalui Fitur Virtual Pada Game Mobile Legends - Ricky Widyananda Putra (Avant Garde, 2023)
With the development of the human mindset and technology in the current period, in communicating not only with conventional media, but at this time in communicating can use other forms of alternative media. One of the media used in communicating is game media. With the presence of online games that use the internet network to play games, it has changed, not only as a mere entertainment medium but has changed to form a "network society" for the players. The online game media that is often used or played by the general public, especially in Indonesia, is the mobile legends game. Communication patterns that are carried out in game media by using virtual features are called virtual communication. This is related to the phenomenon of virtual communication patterns that are currently happening around us. Seeing this phenomenon, here the researchers found the form of problems that exist related to virtual communication, namely how to communicate patterns through virtual features that exist in online mobile legends games for players, especially the creative box community. Researchers conducted using a virtual ethnographic theory approach. This virtual ethnographic approach refers to objects in cyberspace and objects that are described and analyzed in such a way. Researchers use a constructivist paradigm with a qualitative approach methodology. The results obtained in this study are one of the communication patterns that occur in game media by using virtual features in communicating.